The Making of Chicana/o Studies : In the Trenches of Academe. - Acuña, Rodolfo (Latinidad : transnational cultures in the United States., 2011)
The Making of Chicana/o Studies traces the philosophy and historical development of the discipline from precursor movements to the Civil Rights era to today, focusing on the political machinations in higher education that sought to destroy it. As a renowned leader, activist, scholar, and founding member of the movement to establish this curriculum in the California State University system, which serves as a model for the rest of the country, Rodolfo F. Acu±a has, for over four decades, battled the trend in academia to deprive this group of its presence.